Pengaruh Kinerja Akuntansi dan Kinerja Keuangan terhadap Harga Saham (Studi pada Perusahaan Sektor Keuangan yang Listing di Bursa Efek Indonesia) - Tyastari, Tifani Titah Dwi (Jurnal Ilmiah Mahasiswa FEB, 2013)
The stock price reflects the condition of the company. Between stock price and company’s performance has a direct relationship. The companies that have a good performance will have a high stock price too, and conversely. However, investors have to know what factors outside the company that may affect stock price and company’s performance, for example, inflation, economic crisis, interest rates, and foreign exchange rates. The global economic crisis in 2008 led to an adverse impact on most areas in the world. It is also impact to Indonesia, though the effect is not as big as had happened in Europe. However, based on the results of study, the condition of the financial sector stocks in Indonesia is still in good condition. What factorsthat influence investors' decision to buy shares in these conditions becomes important to know, so it can be a benchmark for companies to improve their performance and for investors can be one of knowledge in making an investment decision. Object of this study is the financial sector companies listed in Indonesia Stock Exchange with the study period of 2007-2011. The sampling technique was purposive sampling which consists of 43 companies. This study aimed to examine the effect of accounting performance and financial performance on the stock price. Mechanical testing is multiple regressionusing SPSS Statistics version 17.0. The results of this study indicate that the accounting performance assessment by Operating Income and financial performance assessment by Earnings Per Share has apositive effect on stock price. The financial performance assessment by ROA and ROE negatively affect the stock price. This can occur because the sample is too small and there is a possibility of the influence of the global economic crisis that occurred in the research period. Keywords:      Accounting Performance, Financial Performance, OperatingIncome, Return on Assets(ROA), Return on Equity(ROE), EarningPerShare (EPS), Stock Price